Ethnic, geographic, and seasonal differences of vitamin D status among adults in south‐west China. Issue 12 (26th August 2020) - Li, Lin; Li, Kecheng; Li, Jing; Luo, Yulei; Cheng, Yuheng; Jian, Meiling; Xie, Chunbao; Ji, Chengjie; Chuan, Liangmin; Wang, Zhibin; Li, Haijun; Guo, Xiaolan; et al.
Abstract: Background: There are limited data on vitamin D status of Sichuan province, and no investigation has been carried out on the correlations of 25(OH)D and BTMs between healthy Hans and Tibetans of Sichuan province. This study aimed to examine 25(OH)D levels around Sichuan province and to assess differences by ethnicity, age, gender, sunlight exposure, geographic location, and seasons. Methods: Blood samples from 2317 healthy adults aged of 18 to 75 years and of Han and Tibetan ethnicities were collected in six regions and during four seasons. Serum 25(OH)D2 and 25(OH)D3 levels were measured by LC‐MS/MS method. Serum total P1NP and β‐CTX were measured by immunoassay. Results: Participants aged 18‐40 years showed significantly lower 25(OH)D levels than participants aged 41‐75 years old ( P < .0001). The median serum 25(OH)D level for males was significantly higher than that of females ( P < .0001). Serum 25(OH)D levels among four seasons and different districts varied significantly ( P < .0001). In addition, the 25(OH)D level of Tibetans was significantly lower than that of Hans, while the serum total P1NP and β‐CTX levels of Tibetans were significantly higher than those of Hans ( P < .0001). Conclusion: Adult population was more common to have vitamin D deficiency/insufficiency among Tibetans, females, north regions and in spring and winter. Abstract : This multicenter cross‐sectional study showed that serum 25(OH)D levels of adults in Sichuan province among four seasons and different districts varied significantly ( P < .0001). The 25(OH)D level of Tibetans was significantly lower than that of Hans, while the serum total P1NP and β‐CTX levels of Tibetans were significantly higher than those of Hans ( P < .0001).